Composition of Fatty Acids in Evaluation of Sea Cucumber Potency for Nutraceutical Product Development - Susilowati, Rini; Pratitis, Asri; Januar, Hedi Indra (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2016)
Unsaturated fatty acid in food has an effect to improve human health, while saturated fatty acid has the opposite impact. Ratio between both types of fatty acids is important to evaluate the biological material for nutraceutical product development. This paper aimed to evaluate the nutraceutical potency of sea cucumber from Kendari Bay Waters, South East Sulawesi, based on their fatty acids composition. The analysis was conducted by the 1H-NMR (Hidrogen-Nuclear Magnetic Resonance) method. Several species within 4 genera (Holothuria, Bohadschia, Actinopyga, and Stichopus) were selected as the subject of the study. Comparison of fatty acid composition has been done in genera level, the preliminary study found that variation between species among the same genera was insignificant (p >0.05). Results of the study detected that Holothuria contained with an even ratio of Poly Unsaturated Fatty Acids (PUFA) and Saturated Fatty Acids (SFA), but Actinopyga was detected with low PUFA/SFA ratio. It may suggest that Holothuria from this region is the most potential raw material for nutraceutical product development. Meanwhile, precaution is needed for genera that contained with low PUFA/SFA ratio. Furthermore, comparison with other studies detected that fatty acids composition is not morphological specific, but vary, according to food viability, environmental and geographic location. Therefore, preliminary screening is important in evaluation of sea cucumber material for nutraceutical product development. Â